DRILL BIT SELECTION USING DESIGN OF EXPERIMENTS (DoE) METHOD - Rieza Zulrian Aldio; Zainol Mustafa (Journal of Renewable Energy and Mechanics, 2020)
Drilling process is one of the most common machning process in industrial sector. More than half of the metal-cutting processes are conducted by the drilling process. Drill bit has influenced the results of the drilling process. Therefore, selection of the suitable drill bit becomes a critical factor in the drilling process. This is because the use of the suitable drill bit could fulfill the determined specification value of the hole. Six Sigma and Failure Mode Effect Analysis (FMEA) methods are used to identify factors that have influenced the results of the drilling process. Then by using the Design of Experiment, selection of the best drill bit could be done. In this study, 2 factors that influenced the result are the drill bit type and the drill point angle. Significance test using nested design through MINITAB 14 application has shown that both factors have significant influence over the hole diameter size.. Then by using the plot from the MINITAB 14 application, HPMT 1 became the best drill bit because it could fulfill the specification value. As for the best point angle in this study is 139.72º. Process capability calculation of HPMT 1 has shown that the process is in control. The conclusion is that drill bit HPMT 1 with point angle 139.72º became the best option in this study.